A New Scale for Measuring Identity Insecurity. Issue 1 (2nd January 2023) - Massey, Zachary B.; Cionea, Ioana A.
ABSTRACT: Although theory and research have discussed identity insecurity as a factor that influences intercultural communication behaviors, no reliable measure has been presented to capture this construct. This paper reports results from three studies designed to test and validate a new measure of identity insecurity. Study 1 ( N = 173) included item generation and exploratory factor analysis, revealing five unidimensional identity insecurity factors, termed individual identity insecurity, public presentation insecurity, dissimilar others insecurity, reactive insecurity, and social identity insecurity . Study 2 ( N = 524) confirmed this five-factor structure. Study 3 ( N = 807) further examined the structure and construct validity of the identity insecurity scale. Results confirmed the five-factor solution obtained in Study 2 and revealed the measure had good construct, convergent, and discriminant validity. Thus, we conclude that the proposed new measure for identity insecurity has a clear factor structure, strong factor loadings, and good reliability and validity.